PENGARUH STRUKTUR MODAL, KEBIJAKAN DEVIDEN, DAN STRUKTUR KEPEMILIKAN MANAJERIAL TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2020-2022 - Prisillia, Nadia Yesinta; Munthe, Kornel; Purba, Antonius M; Saragih, Joana L.; Purba, Betniar (Jurnal Manajemen dan Bisnis, 2025)
This research aims to determine and analyze the influence of capital structure, dividend policy and managerial ownership on share prices in manufacturing companies listed on the Indonesia Stock Exchange for the 2020-2022 period. The population in this study was 173 manufacturing companies listed on the Indonesia Stock Exchange for the 2020-2022 period. The sampling technique was purposive sampling, so 18 companies were obtained as samples. The data analysis technique used is multiple linear regression analysis, with the classical assumption test first carried out in the analysis, then hypothesis testing is carried out using the t test and F test. The research results show that partially, capital structure has a positive and significant effect on stock prices, dividend policy has a negative and insignificant effect on stock prices, and managerial ownership has a positive and insignificant effect on stock prices. Simultaneously, capital structure, dividend policy and managerial ownership have a significant effect on share price